Problematika Membolos Teman Sebaya Pada Madrasah Aliyah Swasta Hidayah Desa Bandar Khalifah Tebing Tinggi - Savera, Sari (Journal of Sustainable Education, 2025)
This study aims to analyze the role of peers in truancy behavior among students at the Hidayah Private Islamic Senior High School (MAS) in Bandar Khalifah Village. The method used was a qualitative case study approach. Data were collected through in-depth interviews, observations, and documentation of students who frequently truant, their peers, and their homeroom teachers. The results indicate that peers have a significant influence on truancy behavior. Group solidarity, peer pressure, and fear of rejection are dominant factors driving students to leave school without permission. Furthermore, low learning motivation and weak parental supervision contribute to this behavior. This study concludes that peers play a crucial role in the emergence of truancy. Therefore, collaboration between schools, teachers, and parents is necessary to provide supervision, guidance, and learning motivation to help students reduce truancy.